Gastrin-Releasing Peptide Messenger Ribonucleic Acid Expression in the Hypothalamic Paraventricular Nucleus Is Altered by Melanocortin Receptor Stimulation and Food Deprivation - Ladenheim, Ellen E. (The Endocrine Society, 2009)
Gastrin-releasing peptide (GRP) is a bombesin-like peptide widely distributed in the gastrointestinal tract and central nervous system. In the brain, GRP mRNA is located in the hypothalamic paraventricular nucleus (PVN), a region that receives neural input from the arcuate nucleus and plays a critical role in food intake and energy balance. Because GRP neurons are localized in the vicinity of projection sites in the PVN for peptides that participate in energy homeostasis, we investigated whether GRP mRNA expression in the PVN may be sensitive to challenges imposed by either 38 h food deprivation or stimulation of the melanocortin system by the melanocortin 3/4 receptor agonist, melanotan II (MTII). We found that food deprivation significantly decreased GRP mRNA expression, whereas lateral ventricular MTII administration increased GRP mRNA expression in ad libitum-fed rats 4 h after administration. Furthermore, administration of MTII at a dose that reduces 24 h food intake and body weight prevented the decrease in GRP mRNA expression observed in animals that were pair fed to the amount of food consumed by those injected with MTII. These results demonstrate that food deprivation and stimulation of the melanocortin system produce opposing changes in GRP gene expression in the PVN, suggesting that GRP-containing neurons in the PVN may be part of the hypothalamic signaling pathway controlling food intake and energy balance.